2011
DOI: 10.1039/c2ib00091a
|View full text |Cite
|
Sign up to set email alerts
|

Motility is critical for effective distribution and accumulation of bacteria in tumor tissue

Abstract: Motile bacteria can overcome the penetration limitations of cancer chemotherapeutics because they can actively migrate into solid tumors. Although several genera of bacteria have been shown to accumulate preferentially in tumors, the spatiotemporal dynamics of bacterial tumor colonization and their dependence on bacterial motility is not clear. For effective tumor regression, bacteria must penetrate and distribute uniformly throughout tumors. To measure these dynamics, we used an in vitro model of continuously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
106
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 123 publications
(111 citation statements)
references
References 48 publications
4
106
1
Order By: Relevance
“…These include enhanced bacterial entry and retention in tumors caused by their chaotic and leaky vasculature [22,23] and unimpeded bacterial replication in the anoxic and immunedeficient tumor microenvironment, which lacks macrophage and neutrophil clearance mechanisms [24]. Chemotaxis and active motility of bacteria has also been shown to have a positive influence in the colonization of tumors [25,26]. Intra-vesicle administration of Bacillus Calmé tte-Guerin (BCG) has been used in the clinic during the last decades as the standard treatment for high-grade non-muscle invasive bladder cancer [27], representing a good example of a current anti-cancer therapy in which bacteria is employed to stimulate the immune system in order to promote the killing of cancer cells by a mechanism that is not yet fully understood.…”
Section: Engineered Bacteria Against Cancermentioning
confidence: 99%
“…These include enhanced bacterial entry and retention in tumors caused by their chaotic and leaky vasculature [22,23] and unimpeded bacterial replication in the anoxic and immunedeficient tumor microenvironment, which lacks macrophage and neutrophil clearance mechanisms [24]. Chemotaxis and active motility of bacteria has also been shown to have a positive influence in the colonization of tumors [25,26]. Intra-vesicle administration of Bacillus Calmé tte-Guerin (BCG) has been used in the clinic during the last decades as the standard treatment for high-grade non-muscle invasive bladder cancer [27], representing a good example of a current anti-cancer therapy in which bacteria is employed to stimulate the immune system in order to promote the killing of cancer cells by a mechanism that is not yet fully understood.…”
Section: Engineered Bacteria Against Cancermentioning
confidence: 99%
“…The tumortargeting mechanism of facultative bacteria is complex and is the subject of debate. Generally, there are two opposing theories to explain this mechanism: (1) the chemotactic system and motility of bacteria mediate the successful bacterial colonization of tumors [45][46][47], and (2) a passive mechanism by which inflammatory cytokines are triggered after intravenous injection of bacteria leads to the dilation of tumor blood vessels, allowing the entry of bacteria [48,49]. Work from our group using non-motile Salmonella with a mutation in the flhD gene showed that they accumulate in tumors to an extent comparable to that of motile bacteria (unpublished data).…”
Section: Delivery Of Bacteria To Tumorsmentioning
confidence: 99%
“…Administration of QS Salmonella with exogenous lipid A (12) and enhanced motility (12,38) would increase bacterial density and improve distribution within tumors. Combined, these effects could increase density 253-fold and increase overall drug production.…”
Section: Discussionmentioning
confidence: 99%